22 Comparison of vaginal microbiome and concentrations of estradiol at artificial insemination in Brangus heifers. (28th November 2020) - Messman, Riley D; Contreras-Correa, Zully; Paz, Henry A; Perry, George; Lemley, Caleb O
Abstract: The knowledge surrounding the bovine vaginal microbiome and its implications on fertility and reproductive traits remains incomplete. The objective of the current study was to characterize the bovine vaginal microbiome and estradiol concentrations at time of artificial insemination (AI). Brangus heifers (n = 78) underwent a 7-d Co-Synch + CIDR estrus synchronization protocol. At AI, a double guarded uterine culture swab was used to sample the anterior vaginal tract. Blood samples were collected by coccygeal venipuncture to determine concentrations of estradiol. Heifers were retrospectively classified as pregnant (n = 29) versus nonpregnant (n = 49) on day 35. Lastly, heifers were classified into low (1.1 - 2.5 pg/ml; n = 21), medium (2.6 - 6.7 pg/ml; n = 30), and high (7.2 - 17.6 pg/ml; n = 27) concentrations of estradiol. The vaginal bacterial community composition was determined through sequencing of the V4-V5 region from the 16S rRNA gene using the Illumina Miseq platform. ANOVA was used to compare the diversity metrics between treatment groups. PERMANOVA was utilized to determine variation in community structure. There were no statistical differences in the Shannon diversity index (alpha diversity; P = 0.336) or principal component analysis (beta diversity; P = 0.744) of pregnant versus nonpregnant animals. The vaginal microbiome of pregnant and nonpregnant animals was similar with the four most abundant phyla being Tenericutes, Proteobacteria, Fusobacteria, and Firmicutes. Overall bacterial community composition in animals with high, medium, or low concentrations of estradiol did not differ (P = 0.512). These results indicate that concentration of estradiol does not impact vaginal microbiome composition. In conclusion, the composition of the bovine vaginal microbiome, although dynamic, may not be directly linked to an animal's reproductive ability.